Basic Circulatory Physiology: Interactive Animation and Review Module - Nathaniel (Nick); Michael Brands (Association of American Medical Colleges, 2011)
Abstract The purpose of this module is to present fundamental concepts of basic circulatory physiology using an animate, dynamic visualization of physiological variables as well as an interactive review module. This tool is presented to first-year medical students during the circulatory physiology lecture. It is then used during their personal study time, and is available to them online (as long as they are enrolled in the anatomy and physiology course). This module is currently in use by both first- and second-year medical students as a self-study aid. Students report that this is an effective tool for learning and reviewing the subject matter. Students also report using it both individually and in group study sessions as a study aid.